2023
DOI: 10.1002/joc.8184
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the influences of the selection of the RCP scenario and the reference period on the evaluation results of EURO‐CORDEX simulations for Hungary

Abstract: Temperature and precipitation simulations are evaluated for Hungary based on 11 regional climate model experiments with 0.1° horizontal resolution from the EURO‐CORDEX programme. The aim of the study is to assess the different simulations and the multi‐model (MM) mean as well for 1991–2005 and 2006–2020 separately, on a monthly basis. For the period 2006–2020, three different representative concentration pathway (RCP) scenarios, namely, RCP2.6, RCP4.5 and RCP8.5 are taken into consideration, so the uncertainty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…and Livezey, R.E. (2013) found that using alternative periods is appropriate in the case of temperature, while for precipitation, Kis, A. and Pongrácz, R. (2023) found that the 15-year-long period is capable to represent the variability of the 50-year-long data. We focused only on the summer months (June, July and August) or the spring + summer half-year (from March to August), as water deficit is the most critical in these seasons for cultivated plants and forests.…”
Section: The Analysed Indicesmentioning
confidence: 99%
“…and Livezey, R.E. (2013) found that using alternative periods is appropriate in the case of temperature, while for precipitation, Kis, A. and Pongrácz, R. (2023) found that the 15-year-long period is capable to represent the variability of the 50-year-long data. We focused only on the summer months (June, July and August) or the spring + summer half-year (from March to August), as water deficit is the most critical in these seasons for cultivated plants and forests.…”
Section: The Analysed Indicesmentioning
confidence: 99%